Kemampuan motorik halus melalui teknik finger painting anak down syndrome - Hudayah Taiyeb (Program Studi bimbingan Konseling PPs UNM Makassar, 2016)
The research to improve fine motor ability of Down Syndrome students in terms : painting by using all fingers, by using fingers alternately, eyes-hand coordination. The research is experiment by using descriptive quantitative approach. The design employed Single Subject Research A-B-A. The stage of basaline A1, intervention stage consisted, and basaline A2 consisted. The main data source of the research was Down Syndrome students class VII inisials Tl. Data collection technique used direct observation. The data processed by counting the percentage fine motor ability consisted 3 aspects, namely: painting by using all fingers, painting by using fingers alternately, coordination eyes and hand. The data of the research was analyzed by using quantitative descriptive; then, analyzed by using visual graphic presented in a form of Split-Middle-Technique graphic. The result of intervention given indicates that finger painting technique can improve fine motor of Down Syindrome students in terms of: painting by using all fingers, painting by using fingers alternately, eyes-hand coordination. This improvement through several indicators such as: estimation of direction tendency of each stage which tended to better, the improveme.t of mean level, from basaline A1 to basaline A2, the data overlap percentage from to stage tended to be smaller.